Предмет: Алгебра,
автор: menhuka2675
. Решите уравнение x(х^2 + 6х +9) = -2(x+3).
Ответы
Автор ответа:
0
Ответ: -3; -2; -1
Объяснение:
x(х² + 6х +9) = -2(x+3).
х*(х+3)²+2*(х+3)=0; (х+3)*(х²+3х+2)=0; (х+3)=0 ⇒ х=-3
(х²+3х+2)=0⇒ по Виету х=-1; х=-2
Автор ответа:
1
Ответ:x1= -3,x2= -2,x3= -1
Пошаговое решение:
x³+6ײ+9x=-2x-6
x³+6x²+9x+2x+6=0
x³+x²+5x²+11x+6=0
x³+x²+5x²+5x+6x+6=0
x²×(x+1)+5x×(x+1)+6(x+1)=0
(x+1)×(x²+5x+6)=0
(x+1)×(x²×3x+2x+6)=0
(x+1)×(x×(x+3)+2(x+3))=0
(x+1)×(x+3)×(x+2)=0
x+1=0
x+3=0
x+2=0
x=-1
x=-3
x=-2
Уравнение имеет три решения
x1=-3 x2=-2 x3=-1.
Похожие вопросы
Предмет: Русский язык,
автор: Diko20051
Предмет: Русский язык,
автор: Deniska2202
Предмет: Русский язык,
автор: ValentinGontar
Предмет: Русский язык,
автор: KyTaKbaLLI
Предмет: Физика,
автор: markburmistrovp8f31z